THE EFFECT OF ONLINE CUSTOMER REVIEW TOWARDS PURCHASING INTENTION THROUGH BRAND PERCEPTION AS INTERVENING VARIABLE ON SHOPEE FOOD USERS - Andhy Tri Adriyanto; Agus Prasetyo; Hendra Wijaya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Nowadays, internet has evolved into people lifestyle, including online shopping that has penetrated in selling food. This study aims to determine the effect of online customer review on purchasing intention with brand perception as an intervening variable. The target of this study was Shopee users that located in Semarang City. The population of this study covered Shopee users in Semarang City with 96 respondents as sample. Research data was taken from two sources, namely primary data and secondary data. This is categorized as quantitative research with census technique sampling. Data that had been collected was analyzed using Structural Equation Modeling (SEM) with SmartPLS version 3.2 software. The results of this study shows that Online Customer Review has a significant effect on Brand Perception and Purchasing Intention, while Brand Perception has a significant effect on Purchasing Intention. Brand Perception variables was able to mediate the relationship between the effect of Online Customer Review towards Purchasing Intention.